Perioperative Management of Marfan Syndrome in Pregnancy and Congestive Heart Failure - Koeshardiandi, Mirza; Mudianto, Fajar Tri; Himawan, Muhammad Wildan Afif; Abuajwa, Ahmed Eliaan Shaker; Semedi, Bambang Pujo (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: A mutation in fibrillin-1 (FBN1) leads to the autosomal dominant condition known as Marfan Syndrome (MFS). The condition of pregnancy with MFS may increase morbidity and mortality during pregnancy and delivery. Due to a greater frequency of maternal problems and fetal involvement, pregnancy with Marfan syndrome (MFS) provides challenges to healthcare professionals and patients and requires special treatment. Objective: This study aimed to analyze the perioperative management of Marfan syndrome in pregnancy and congestive heart failure (CHF). Case report: A 27-year-old primigravida with 38-39 weeks gestation presented with a referral letter with a diagnosis of G1P0A0 with scoliosis and peripartum cardiomyopathy. The patient complained of shortness of breath accompanied by cold sweat since the second trimester of gestation. Physical examination revealed the presence of arachnodactyly and spine deformity. The patient underwent an emergency cesarean section with general anesthesia. Breathing problem appeared the next day after cesarean section, the patient was intubated in the ICU. Chest X-ray depicted bilateral pulmonary edema. A mechanical ventilator was set up and fluid restriction had been done. The patient was extubated after showing breathing improvement in the second week in the ICU. The diagnosis of MFS in this patient was defined based on the revised Ghent Nosology. MFS with spine deformity causes breathing problems because of the altered geometry of the thoracic cavity. MFS in pregnancy may worsen the breathing problem due to autotransfusion that leads to pulmonary edema. A mechanical ventilator with a specific setting accompanied by fluid restriction is recommended to reduce the fluid overload in the lungs. Conclusion: Mechanical ventilators with specific settings and fluid restriction are effective perioperative management to reduce pulmonary edema on MFS in pregnancy and congestive heart failure.